Cruise Management Information and Decision Support Systems - Papathanassis, Alexis.; Papathanassis, Alexis.; Breitner, Michael H.; Breitner, Michael H.; Schoen, Cornelia.; Schoen, Cornelia. (Gabler Verlag : Imprint: Gabler Verlag, 2012)
Increasingly, cruise operators are utilising information and communication technologies (ICTs) to improve service-effectiveness and process efficiency, both on- and off-board. Therefore, it is worth initiating a discussion on the potential and challenges ICTs entail for both cruise operators’ back-offices and for cruisers’ consumption experiences. This book documents the proceedings of the 1st e-Cruising Conference (Bremerhaven, Germany), which was aimed at discussing the possibilities and applicability of ICTs and mobile services in various aspects of cruise operations. Following a rigorous double-blind review, the best papers were chosen to be incorporated in this volume.